Conflict as a closure: A Kaleckian model of growth and distribution under financialization - Srinivas Raghavendra; Petri T. Piiroinen (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2019)
In this paper, we show how the conflict between the shareholders (owners) and managers of firms in terms of profit rates generates dynamics between growth and distribution that results in a long-run variation in the capacity utilization rate. The model developed here generates oscillations in the rate of capacity utilization in the short run before settling down to its long-run value. Furthermore, the long-run value of the rate of capacity utilization falls within a range of plausible values and this range is determined by the conflict between shareholders and managers. The conflict as a closure, we believe, provides a more realistic microeconomic underpinning to study the impact of distribution on accumulation and long-run utilization. In doing so, we have not taken the approach of the existence of normal utilization rate that is relied upon by the Harrodian authors (Skott 2008, Skott and Ryoo, 2008) and the endogenization of animal spirits in such a way that the actual utilization influences the desired or normal rate of utilization by the Kaleckian authors (Hein 2012, Lavoie, 2003). The model yields hysteresis in that it generates two different disequilibrium growth paths when shareholders and managers struggle to gain control of the firm.
Keywords: E11; E12; D21; E25; E32; 330; Capital accumulation; Rate of capacity utilization; Conflict; Rate of profit; Long run Equilibrium; Hysteresis; Efficient frontier; Finance frontier; Leverage ratio; Shareholders; Managers; Power struggle